Laparoscopic Salvage of Malfunctional Peritoneal Dialysis Catheters. Outcome and Patency in 37 Patients - Janwanitchsthaporn, Sorawat; Sriphatphiriyakun , Phaiwit; Pongampai, Suparerk (The Thai Journal of Surgery, 2023)
Background: There are more than 100,000 patients in Thailand who require long-term renal replacement therapy, and the number continues to grow significantly. Peritoneal dialysis is a viable option with some advantages over hemodialysis. However, malfunction of peritoneal dialysis catheters is the major problem in these patients. Laparoscopic salvage of the catheters can resolve the major cause of malfunction. Objective: To evaluate the success rate and safety of laparoscopic salvage of malfunctioning peritoneal dialysis catheters and the patency of salvaged catheters in Suratthani Hospital. Methods: In this retrospective descriptive study, 42 patients who underwent laparoscopic salvage of malfunctioning peritoneal dialysis catheters at Suratthani Hospital were included. All the salvage procedures were performed under general anesthesia using one 10 mm and two 5 mm ports. The various techniques to rescue catheter function included re-positioning the catheter with pelvic fixation, clearing the fibrin clot/sheath, freeing up the omental, adhesion, and partial omentectomy. All patients were followed up for at least 6 months or until using peritoneal dialysis discontinuing. Results: A total of 42 laparoscopic salvage of catheter malfunctions were attempted and succeeded in 37 cases. The mean operative time was 62.4 minutes. The omental wrapping was the most common cause of catheter malfunction (62.1%). The catheter patency rate was 83.7%, 62.1%, 45.94%, and 24.32% at 1 month, 6 months, 12 months, and 24 months respectively. Conclusion: Laparoscopic salvage of malfunctioning peritoneal dialysis catheters seems feasible and safe to recuse and prolong peritoneal dialysis catheter usage. Our findings will provide insight for surgeons in salvaging peritoneal dialysis catheter malfunction.